The importance of dystrophin and the dystrophin associated proteins in vascular smooth muscle - Kaplan, Katherine M.; Morgan, Kathleen G. (Frontiers in Physiology, 2022)
This review will detail the role of dystrophin and the dystrophin associated proteins (DAPs) in the vascular smooth muscle (VMS). Dystrophin is most comprehensively studied in the skeletal muscle due to serious symptoms found related to the skeletal muscle of patients with muscular dystrophy. When mutations in the dystrophin gene, or DAPs genes, ensue different muscular dystrophies occur. In skeletal muscle, dystrophin is known to act to as a cytoskeletal stabilization protein and defends cells against damage due to contraction. In skeletal muscle, Dystrophin stabilizes the plasma membrane by transmitting forces generated by sarcomeric contraction to the extracellular matrix (ECM). Dystrophin is a scaffold that binds the dystroglycan complex (DGC) and has many associated proteins (DAPs). These DAPs include sarcoglycans, syntrophins, dystroglycans, dystrobrevin, neuronal nitric oxide synthase and caveolins. The DAPs provide biomechanical support to the skeletal or cardiac plasma membrane during contraction, and loss of 1 or several of these DAPs leads to plasma membrane fragility. Dystrophin is expressed near the plasma membrane of all muscles, including cardiac and vascular smooth muscle, and some neurons. Dystrophic mice have noted biomechanical irregularities in the carotid arteries and spontaneous motor activity in portal vein altered when compared to wild type mice. Additionally, some studies suggest the vasculature of patients and animal models with muscular dystrophy is abnormal. Although the function of dystrophin and the DAPs in VSM is not thoroughly established in the field, this review makes the point that these proteins are expressed and important.